PREDICTION OF GTE VANES DEFLECTION BY ANALYTICAL MODELS OF TECHNICAL AND GEOMETRIC INITIAL DATA IN CROSS LINE MILLING ON MULTI-AXIS CNC MACHINES - Svirshchev, Valentin I.; Tarasov, Stepan V.; Merezhnikov, Vladislav (Journal of Applied Engineering Science, 2023)
In the process of milling the profile of the vanes of a gas turbine engine on multi-operational machines, a technological scheme of transverse line shaping is used. According to this scheme, the vane rotates around its own axis, it is machined with a mill with a spherical working surface, which performs rotation and interpolated axial movement. The required parameters of the surface quality of the vane airfoil profile (profile accuracy and surface roughness parameter) are provided by assigning a combination of controlled processing parameters. However, today there are no recommendations on the calculation and assignment of combinations of controlled parameters for the milling of complex-profile surfaces, which is the profile of the flow path of the GTE compressor vanes. For each line and angle of rotation of the vane, the accuracy of the vane profile will be determined depending on the amount of vane deformation, which should not exceed the tolerance for its manufacture. In the course of the analysis of geometric relationships in the contact zone of the curved profile of the flow part of the vane and the mill with a spherical working surface, dependences were obtained to determine the magnitude of the force component during milling and its projection on the Y axis, as well as the effective diameter of the mill, which are necessary to calculate the magnitude of the total deformation of the vane. A methodology is proposed and analytical models are obtained for determining and assigning a combination of controlled parameters of the milling mode that provide a given accuracy of the vane airfoil profile when developing a control program for the vane milling process on a CNC machine.